Comparison of the efficacy of bilateral approach PVP and lateral hole injection combined with modified fluoroscopic unilateral approach PVP in the treatment of thoracolumbar osteoporotic fractures - Yuan Jianmin; Fu Jianguo; Ma Nengfeng; Wu Xingjing; Xie Jiabing; Tao Zhoushan; Cheng Wenjing; Lu Jingshun (BMC Surgery)
Abstract Objective To compare the clinical efficacy of bilateral approach PVP and lateral injection combined with modified fluoroscopic unilateral approach PVP in the treatment of thoracolumbar osteoporotic fractures. Methods The clinical data of 100 patients with thoracolumbar osteoporotic fractures who received treatment in our hospital from January 2018 to January 2021 were retrospectively collected. According to the different surgical methods, group A included 48 patients who received bilateral approach PVP. Group B was composed of 52 patients who received lateral injection combined with modified fluoroscopy. General data, intraoperative data, and postoperative follow-up data of the two groups of patients were collected and statistically analyzed. Results There was no significant difference in the general data between the two groups (P > 0.05), and the two groups were comparable. In terms of intraoperative data, the operation time of group B was shorter than that of group A, and the difference was statistically significant (P < 0.05). The number of intraoperative fluoroscopies in group B was less than that in group A, the difference was statistically significant (P < 0.05), while patients in group A had a higher bone cement leakage rate, and the difference was statistically significant (P < 0.05). In terms of postoperative follow-up, there was no statistically significant difference in VAS and ODI scores 1 day before surgery between the two groups (P > 0.05), and statistically significant difference in VAS scores 1 day after surgery, 1,3 and 6 months after surgery between the two groups compared with 1 day before surgery (P < 0.05). The ODI scores 1,3 and 6 months after surgery were statistically significant compared with 1 day before surgery (P < 0.05), while the VAS and ODI scores of the two groups were not statistically significant 1 day after surgery and 1,3 and 6 months after surgery (P > 0.05). Conclusion Compared with the bilateral approach PVP, lateral injection combined with improved fluoroscopy has the advantages of shorter operation time, fewer intraoperative fluoroscopy times, and lower bone cement leakage rate.